Differences in the Quantity and Quality of Organic Matter Exported From Greenlandic Glacial and Deglaciated Watersheds. Issue 10 (21st October 2020) - Pain, Andrea J.; Martin, Jonathan B.; Martin, Ellen E.; Rahman, Shaily; Ackermann, Philip
Abstract: Riverine input of terrestrial dissolved organic matter (DOM) is an important component of the marine carbon cycle and drives net carbon dioxide production in coastal zones. DOM exports to the Arctic Ocean are likely to increase due to melting of permafrost and the Greenland Ice Sheet, but the quantity and quality of DOM exports from deglaciated watersheds in Greenland, as well as expected changes with future melting, are unknown. We compare DOM quantity and quality in Greenland over the melt seasons of 2017–2018 between two rivers directly draining the Greenland Ice Sheet (meltwater rivers) and four streams draining deglaciated catchments that are disconnected from the ice (nonglacial streams). We couple these data with discharge records to compare dissolved organic carbon (DOC) exports. DOM sources and quality differ significantly between watershed types: fluorescence characteristics and organic molar C:N ratios suggest that DOM from deglaciated watersheds is derived from terrestrial vegetation and soil organic matter, while that in glacial watersheds contains greater proportions of algal and/or freshly produced biomass and may be more reactive. DOC specific yield is similar for nonglacial streams (0.1–1.2 Mg/km 2 /year) compared to a glacial meltwater river (0.2–1.1 Mg/km 2 /year), despite orders of magnitude differences in instantaneous discharge. Upscaling based on land cover leads to an estimate of total DOC contributions from Greenland between 0.2 and 0.5 Tg/year, much of which is derived from deglaciated watersheds. These results suggest that future warming and ice retreat may increase DOC fluxes from Greenland with consequences for the Arctic carbon cycle. Key Points: Specific yield of dissolved organic carbon (Mg/km 2 /year) is similar between Greenlandic glacial and deglaciated watersheds Sources and potential reactivity differ between glacial (algal) and nonglacial (terrestrial vegetation and soils) watersheds Upscaled organic carbon export from deglaciated watersheds is currently similar to that from glacial watersheds but may increase with future warming